INFORMATION SYSTEM FOR ANALYSIS OF DIAGNOSTIK TECHNOLOGIES OF VIRAL INFECTIONS - Шпурик, Вадим; Бандурка, Елена; Соловьев, Сергей (SWorldJournal, 2021)
The theoretical evaluation and the example of practical implementation of the automation of appraising and pharmacoeconomic efficiency forecasting of the diagnostic technologies to detect viruses of human infectious diseases based on developed software ar